Droit des signes distinctifs: marques, nom commercial - Cruquenaire, Alexandre (Droit de l'informatique et des technologies de l'information : chronique de jurisprudence : 1995-2001, 2003)
Keywords: case law; cybersquatting; domain names; out-of-court settlement; trade name; trademark law; udrp

Rethinking consumer protection policy - Trebilcock, Michael (International Perspectives on Consumers' Access to Justice, 2003)
This is the version of record of an article authored by Michael Trebilcock and published by the Cambridge University Press.